A new geopolitical positioning of South Africa: Strategies for a modern "Swing State" - Ralph Wrobel (OrdnungsPolitisches Portal (OPO), 2026)
The evolving geopolitical landscape has placed South Africa at a crossroads, torn between its historical ties to the West and its growing relationships with BRICS+ nations, particularly China and Russia. The country's recent political shift, marked by the African National Congress (ANC) losing its parliamentary majority, has intensified debates over its international alignment. As a "Global Swing State," South Africa must navigate a complex global order by balancing cooperation with both power blocs-mainly Europe and China-while maintaining independence. A pragmatic foreign policy-one that prioritises economic development, democratic stability, and institutional reform- will be crucial in positioning South Africa as a bridge between the Global South and the West.
Keywords: F50; O55; P45; 330; Geopolitics; Swing States; South Africa; Europe; Russia; China